The development of nursing-sensitive indicators: A critical discussion - Edel Gormley; Michael Connolly; Mary Ryder (Elsevier, 2024)
Discussion arguments: In a science-based profession, nurses must continuously monitor and evaluate the effectiveness of their care. However, data on what constitutes nursing care in practice and the delivery process is lacking. Insufficient evidence on how nurses contribute to patient care hampers the evaluation of nursing practice.We discuss nursing-sensitive indicators, their origins, current applications, and challenges related to their use in evaluating the quality of nursing care. We analyse nursing-sensitive indicators in the context of criticisms levelled at the profession related to the lack of evidence to support their value in the larger healthcare environment. Conclusions: We have a disjointed approach to evaluating nursing care. Current systems designed to monitor nursing care, such as metrics and data sets, are not adequate or effective for comprehensively evaluating nursing care, considering the fundamentals and values of the nursing profession.